Vaccine Literacy and Hesitancy on routine and travelers’ vaccines: a preliminary online survey - Biasio, Luigi Lorenzo; Lorini, Chiara; Pecorelli, Sergio (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The vast amount of conflicting information during the COVID-19 pandemic might have had a detrimental effect on people’s opinions about vaccinations, including groups like travelers. This study aimed at assessing Vaccine Literacy in a sample of the general Italian population, together with antecedents of Vaccine Hesitancy, such as confidence, complacency, and convenience, the so-called “3Cs”, and their effects on accepting routine and travelers’ vaccines. Study Design. A specifically designed anonymous questionnaire was created by using Google forms and validated through a face validity process. Subsequently, it was employed in an online cross-sectional survey. Methods. The assessment Vaccine Literacy scale used in this survey was similar to that employed in earlier surveys. In addition to demographic data and information sources used by participants, the questionnaire was composed, in total, of nine multiple choice questions on Vaccine Literacy, and six questions on the 3Cs. Considered outcomes were self-reported participants’ beliefs, attitudes, behaviors and intentions toward recommended routinary adulthoods vaccines and arboviral vaccines for travelers. A section of the questionnaire focused on chikungunya awareness, taken as an example of arboviral disease that has caused outbreaks in Italy, but not yet vaccine-preventable at the time of the investigation. Results. After cleaning the database, 357 responses were suitable for analysis. Vaccine Literacy mean functional score was 2.81 ± 0.74 (lower than in an earlier survey, p = 0.012), while the interactive-critical (score 3.41 ± 0.50) was higher (p<0.001). Vaccine literacy was confirmed to be associated with attitudes and behaviors towards vaccination, with the 3Cs often acting as a mediator. However, interactive Vaccine Literacy was misaligned with respect to functional and critical ones, as if looking for information sources or discussing about vaccination was less relevant than amidst the pandemic. Also, there was an increase in Vaccine Hesitancy, particularly with regard to travel vaccinations, with 10-17% of individuals refusing to be vaccinated if travelling in areas at risk. The main limitation of the study was the unbalance in demographic variables, in particular the education level. Conclusions. The study highlights the risks associated with current travel, including those related to climate change and the spread of vector-borne infections. It underscores the importance of raising awareness about arboviral diseases and the vaccines available to prevent them. As with all online surveys that employ convenience sampling, this study might not have provided a comprehensive representation of the entire population. Nevertheless, a dedicated analysis has been conducted to reduce biases and make data interpretation easier. Despite the need for further research, the findings indicate potential new approaches for assessing Vaccine Literacy and Vaccine Hesitancy, to ease the development of new communication strategies to enhance routine and travel vaccinations